A clinical study in distal femur fractures management with locking compression plate without C-arm images - Singla, Gaurav (International Journal of Research in Orthopaedics, 2019)
Background: Distal femur fractures pose a surgical challenge to the orthopaedic surgeons. Multiple implants are available but locking compression plate is a good implant to be used in this anatomical location. LCP may reduce the tendency of varus collapse and offers higher stability than other implants. Aim of our study was to review functional outcome, union time and complications in distal femoral fractures treated with distal femoral locking plate without C-arm imaging modality. Methods: 25 patients with closed or open type grade1 and 2 distal femur fractures managed with open method locking compression plate without C-arm image. Pritchett rating system was used for evaluation of outcome. Results: All patients in this series united well with an average time of 13 weeks with minimal complications. Functional outcome was excellent in 4 patients, good in 19 patients, fair in 2 patients. Conclusions: Open reduction and locking compression plate is suitable implant available for fixation of distal femur fractures with minimal complications. Even it can be done without C-arm. Surgical technique and proper anatomical reduction and alignment are the key for good results.